A Keystone Gut Bacterium Christensenella minuta—A Potential Biotherapeutic Agent for Obesity and Associated Metabolic Diseases - Wei-Shan Ang; Jodi Woan-Fei Law; Vengadesh Letchumanan; Kar Wai Hong; Sunny Hei Wong; Nurul Syakima Ab Mutalib; Kok-Gan Chan; Learn-Han Lee; Loh Teng-Hern Tan (Foods, 2023)
A new next-generation probiotic, Christensenella minuta was first discovered in 2012 from healthy human stool and described under the phylum Firmicutes. C. minuta is a subdominant commensal bacterium with highly heritable properties that exhibits mutual interactions with other heritable microbiomes, and its relative abundance is positively correlated with the lean host phenotype associated with a low BMI index. It has been the subject of numerous studies, owing to its potential health benefits. This article reviews the evidence from various studies of C. minuta interventions using animal models for managing metabolic diseases, such as obesity, inflammatory bowel disease, and type 2 diabetes, characterized by gut microbiota dysbiosis and disruption of host metabolism. Notably, more studies have presented the complex interaction between C. minuta and host metabolism when it comes to metabolic health. Therefore, C. minuta could be a potential candidate for innovative microbiome-based biotherapy via fecal microbiota transplantation or oral administration. However, the detailed underlying mechanism of action requires further investigation.